(3CNHGQ GdHdOGfs - (3CHh YHO Gddg CMeO Hf eMeO Hf ESMGb Hf EHQGgje GdgePGfj Hf Gdabjg,J (B365 (3g` s
(3ChdgG (B:s
(3GdMeO ddg gPG HbjI Gdbhd Ydi GdYQGb hGdHUQI hCNHGQ aJMgG , hdhbJ GdPi HfjJ , heG ajgG ef GdYLGFH , hGdbhd ai GdCHdI , hGdbhd ai GdHWGFM , hGdbhd ai hGSW s
(3BNQgG (B:s
(3ef YfhGf (B: (3CdbGH edhc NQSGf hGdeTQb hGdJQc hGdfhGMi GdedJUbI Hge , bhdg (B: (3CeG edhc GdJQc (B: (3gjdhH NdbGf , NHZhf TGHg NGbGf , SfLjQ NGbGf TgQGf ZhQc Je GdcJGH HMeO Gddg Edi gGgfG s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B251s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B260 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B405 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQVhjI (B_ (3eTgO (B(5229) s
Keywords: (3GdJGQjNs